1981
DOI: 10.1021/je00024a020
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a gaseous mixture of ethane and propane on a carbon molecular sieve

Abstract: The adsorption of a binary gaseous mixture of ethane and propane on the carbon molecular sieve MSOSA was measured at temperatures of 5, 30, and 50 °C and a pressure of 100 mmHg and at 30 °C and 300 mmHg. The amount of propane adsorbed was much higher than the value predicted by the method of Myers and Prausnltz. This preference for propane was greater at lower temperatures but did not change with pressure. Activity coefficients of the adsorbed phase calculated by the Myers-PrausnHz method showed that, at very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…7. Comparable results were reported by Nakahara et al (1981) for the adsorption of mixtures of ethane and propane on a carbon molecular sieve. However, the results of the present study are not in agreement with those reported by Buss (1995) in a similar study on equilibrium adsorption of carbon dioxide-methane mixtures on a large pore activated carbon with low energetic heterogeneity.…”
Section: Discussionsupporting
confidence: 69%
“…7. Comparable results were reported by Nakahara et al (1981) for the adsorption of mixtures of ethane and propane on a carbon molecular sieve. However, the results of the present study are not in agreement with those reported by Buss (1995) in a similar study on equilibrium adsorption of carbon dioxide-methane mixtures on a large pore activated carbon with low energetic heterogeneity.…”
Section: Discussionsupporting
confidence: 69%
“…6 PCB activated carbon (Ritter and Yang, 1987). c Molecular sieve carbon (Nakahara et al, 1981). d Silica (Markham and Benton, 1931).…”
Section: Resultsmentioning
confidence: 99%
“…Binary mixture adsorption equilibria on molecular sieve carbon 5A at 303 K and 100 Torr. ( ) C3H8-C2H6 (Nakahara et al, 1981), (O) C2H4-C3H6 (Nakahara et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of Predictions of Binary Mixture on Molecular Sieve Carbon 5A(Nakahara et al, 1981(Nakahara et al, , 1982Konno et …”
mentioning
confidence: 99%